2018
DOI: 10.1016/j.jot.2018.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Surgical masks as source of bacterial contamination during operative procedures

Abstract: BackgroundSurgical masks (SMs) are used to reduce bacterial shedding from the mouth, nose and face. This study aimed to investigate whether SMs may be a potential source of bacterial shedding leading to an increased risk of surgical site infection.MethodsBacterial contamination of the SMs was tested by making an impression of the external surface of the mask on sterile culture media immediately. We investigated the difference in bacterial counts between the SMs worn by surgeons and those placed unused in the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
71
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(84 citation statements)
references
References 17 publications
5
71
1
Order By: Relevance
“…Inclusion criteria were (1) study type: RCT (including cluster‐randomized trial) and nonrandomized controlled study; (2) participants: humans with influenza (including pandemic strains, seasonal influenza A or B viruses and zoonotic viruses such as swine or avian influenza), and other respiratory viral infections (as a proxy for influenza); (3) intervention and comparator: N95 respirators versus surgical masks; (4) primary outcome: laboratory‐confirmed influenza; (5) secondary outcomes: laboratory‐confirmed respiratory viral infections, laboratory‐confirmed bacterial colonization, laboratory‐confirmed respiratory infection, and influenzalike illness; and (6) settings: hospital or community. RCTs were selected due to the potential possibility of high evidence level.…”
Section: Methodsmentioning
confidence: 99%
“…Inclusion criteria were (1) study type: RCT (including cluster‐randomized trial) and nonrandomized controlled study; (2) participants: humans with influenza (including pandemic strains, seasonal influenza A or B viruses and zoonotic viruses such as swine or avian influenza), and other respiratory viral infections (as a proxy for influenza); (3) intervention and comparator: N95 respirators versus surgical masks; (4) primary outcome: laboratory‐confirmed influenza; (5) secondary outcomes: laboratory‐confirmed respiratory viral infections, laboratory‐confirmed bacterial colonization, laboratory‐confirmed respiratory infection, and influenzalike illness; and (6) settings: hospital or community. RCTs were selected due to the potential possibility of high evidence level.…”
Section: Methodsmentioning
confidence: 99%
“…(20) Mathematical models to assess the likely effectiveness of facemasks on the reproduction number (R) have highlighted the importance of the filtration efficacy. (26) The third-party and self-contamination risk increases with the working life of a protective mask (27,28) ; therefore, a regular change or a regular cleaning is mandatory. It is assumed that the moisture in the mask cloth as well as the contamination rate of the mask with airborne pathogens increases significantly with longer use of the masks.…”
Section: Fig 2 Box Plot Of the Measured Filtration Efficacy Statismentioning
confidence: 99%
“…(29) Infectious particles from the mask surface could be further spread by contact or re-aerosolization causing self-infection or infection of others. (27)(28)(29) With regard to the change intervals and hygienic preparation, it is advisable not to exceed a total wearing time of 6 hours. (27) The mask should then be disinfected.…”
Section: Fig 2 Box Plot Of the Measured Filtration Efficacy Statismentioning
confidence: 99%
“…In respect to improper wearing of mask, higher percentage of 69% among study participants of Ebrahimpour et al, [21] pull the mask under their chin which is against the infection control principles as reported by CDC [7]. These guidelines reported that contaminated mask could contaminate the rest of the scrub attire and according to assumption of Zhiqing et al, [25] surgical masks could be the source of bacterial shedding with extended wearing time.…”
Section: Student Clinics At Umm Al-qura Dental Teachingmentioning
confidence: 98%